Efektivitas Penilaian Mandiri Evaluasi Menuju Wilayah Bebas dari Korupsi/Wilayah Birokrasi Bersih Melayani di Kementerian Kesehatan dalam Rangka Pelaksanaan Kebijakan Reformasi Birokrasi - Dora Dora; Wachyu Sulistiadi (Jurnal Kebijakan Kesehatan Indonesia, 2019)
Self Assessment  Effectiveness of Free of Corruption Area/Clean and Serve Bureaucratic Area Evaluation in The Health Ministry in The Aim of Bureaucracy Reform Policy Background: Implementation of Bureaucratic Reform has an important role in supporting the implementation of national development in the field of health. Strengthening Bureaucracy Reform aims to improve public services because bureaucrats are public servant. Evaluation towards WBK / WBBM is a small form of Bureaucracy Reform applied to a minimum work unit of echelon 3. Evaluation to WBK / WBBM was conducted through self assessment by Internal Assessment Team at Ministry of Health level, which will be futher evaluate by National Assessment Team from Ministry of Empowerment of State Apparatus and Bureaucracy Reform. There is a significant difference between the evaluation results conducted by TPI and TPN. Purpose: The purpose of this study is to determine the effectiveness of self assessment  in the evaluation of WBK / WBBM conducted by Itjen Kemenkes in accelerating the achievement of Bureaucracy Reform in the Ministry of Health. Method: This research is a descriptive study with qualitative analysis method by conducting in-depth interviews with 9 informants and document tracking. Results: The study was conducted in May - June 2017, located in DKI Jakarta area. The result of the research stated that the regulation is not yet complete, the communication of the evaluation implementation clear, the leader has not fully understand about WBK / WBBM, there is still conflict of interest, there are differences of work unit characteristic, there is still difference of motivation, perception and human resource competence become a factors that influence effectiveness of the evaluation towards WBK / WBBM in the Ministry of Health. Conclusion: Self Assessment  implementation  towards WBK / WBBM evaluation in Ministry of Health have not effective so require evaluation and further improvement.Keywords: Bureaucracy Reform, Free Area of Corruption, Clean and Serve Bureaucratic AreaLatar Belakang: Pelaksanaan Reformasi Birokrasi memiliki peran yang penting dalam mendukung mendukung pelaksanaan pembangunan nasional di bidang kesehatan. Penguatan Reformasi Birokrasi bertujuan untuk memperbaiki pelayanan publik karena birokrat adalah pelayan kepentingan masyarakat. Evaluasi menuju WBK/WBBM adalah bentuk kecil dari Reformasi Birokrasi yang diterapkan kepada satuan kerja minimal setingkat eselon 3. Evaluasi menuju WBK/WBBM dilakukan secara penilaian mandiri oleh Tim Penilai Internal di tingkat Kementerian Kesehatan, yang pada tahap lanjut akan dilakukan oleh Tim Penilai Nasional dari Kementerian Pendayagunaan Aparatur Negara dan Reformasi Birokrasi. Terdapat perbedaan yang cukup signifikan antara hasil evaluasi yang dilakukan oleh TPI dengan TPN. Tujuan: Tujuan penelitian ini untuk mengetahui efektivitas penilaian mandiri dalam evaluasi WBK/WBBM yang dilakukan Itjen Kemenkes dalam mempercepat tercapainya Reformasi Birokrasi di Kementerian Kesehatan.  Metode: Penelitian ini merupakan studi deskriptif dengan metode analisis kualitatif dengan melakukan wawancara mendalam terhadap 9 informan dan penelusuran dokumen. Hasil: Penelitian dilakukan pada bulan Mei - Juni 2017, berlokasi di wilayah DKI Jakarta. Hasil penelitian menyebutkan bahwa regulasi belum lengkap, komunikasi pelaksanaan evaluasi sudah jelas, pemimpin belum memahami sepenuhnya mengenai WBK/WBBM, masih terdapat benturan kepentingan, terdapat perbedaan karakteristik satuan kerja, masih terdapat perbedaan motivasi, persepsi dan kemampuan sumber daya manusia menjadi faktor yang berpengaruh dalam efektifitas pelaksanaan evaluasi menuju WBK/WBBM di Kementerian Kesehatan.  Kesimpulan: Pelaksanaan Penilaian mandiri  evaluasi menuju WBK/WBBM di Kementerian Kesehatan belum efektif sehingga memerlukan evaluasi dan perbaikan lebih lanjut.